1991
DOI: 10.1073/pnas.88.19.8582
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a neu/c-erbB-2 protein-specific activating factor.

Abstract: The neu oncogene encodes a tyrosine kinase with growth factor receptor-like properties. A neu proteinspecific activating factor (NAF) was partially purified from medium conditioned by the transformed human T-cefl line ATL-2. NAF was able to stimulate the tyrosine-specific kinase activity of the neu protein (p185"), induce dimerization and internalization, and increase the growth ofcells bearing the neu protein. The effects of NAF were mediated by an interaction with the pl85" extracellular domain. NAF had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…We propose that overexpression of the neu receptor causes the formation of multimeric receptors resulting in constitutive activation that ultimately leads to transformation. Since overexpression of the c-erbB2 protein has been observed in several human cancers (1,11,21,30), these studies provide a physicochemical explanation for the activated forms of amplified receptor species. The conversion of monomeric p185c-neu to the multimeric form also develops as a consequence of specific binding of the ligand to its extracellular ligand-binding domain of the receptor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that overexpression of the neu receptor causes the formation of multimeric receptors resulting in constitutive activation that ultimately leads to transformation. Since overexpression of the c-erbB2 protein has been observed in several human cancers (1,11,21,30), these studies provide a physicochemical explanation for the activated forms of amplified receptor species. The conversion of monomeric p185c-neu to the multimeric form also develops as a consequence of specific binding of the ligand to its extracellular ligand-binding domain of the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…A factor of 25 kDa has been isolated from bovine kidney and is mitogenic for NIH 3T3, DHFR-G8, and A431 cells (10). We have isolated and characterized a neuactivating factor (NAF) from a transformed human T-cell line (11). The NAF ligand specifically interacts with the neu extracellular domain, resulting in neu-specific tyrosine kinase activation, receptor dimerization, internalization, and concomitant potentiation of the growth of neu receptorexpressing cell lines.…”
mentioning
confidence: 99%
“…Because the c-ras and c-myc oncogenes were both involved in cellular transformation and/or apoptosis pathway in cooperation with TP53 (Finlay et al, 1989), we analyzed these 2 genes in the N 2 breast tumors. The c-erbB-2/neu gene, which encodes a transmembrane protein with extensive homology with the epidermal-growth-factor receptor (Dobashi et al, 1991), has been found to be amplified and over-expressed in 10-to 50% of N 1 breast cancers. In N 2 breast cancer, the prevalence is somewhat lower (10 to 20%), but the prognostic value of c-erbB-2/neu is now well established in this group of patients (Press et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ErbB-2 can be transphorylated by either ErbB-3 and ErbB-4 following the stimulation of mammary tumor cell lines with Neuregulins which are speci®c ligands for ErbB-2 and ErbB-4. By contrast, no direct ligand has been cloned for ErbB-2 although several activities have been puri®ed for some time (Dobashi et al, 1991;Lupu et al, 1992;Samanta et al, 1994;Wu et al, 1994;Heldin, 1995;Tzahar and Yarden, 1998).…”
Section: Erbb-2 Plays a Causal Role In Mammary Tumorigenesismentioning
confidence: 99%